Comparison of emotion evaluation perception using human voice signals of robots and humans - Kirandziska, Vesna; Ackovska, Nevena (My University, 2013)
Emotion perception is the process of perceiving other people’s emotions. It can be based on their facial expression, movement, voice and other biosignals people emit. The evaluation of human’s emotion is one characteristic of emotions. One of the research areas in Robotics is adapting humanistic behavior in robots. Today many robots are constructed. Some of them can even perceive emotions. In this paper a custom built emotion aware robot that perceives emotion evaluation is used to investigate the similarity and differences of the robot's and human's emotion perception. Voice signals from real human were recorded and the information for the emotion evaluation was obtained from our robot, but also from a set of human evaluators. This paper presents the results of the experiments done. The experimental results show the difficulty of the problem of emotion evaluation perception in general. The significance of human voice signals in emotion evaluation is also investigated.
Keywords: emotion, evaluation, robots, human